2006
DOI: 10.1029/2005gb002558
|View full text |Cite
|
Sign up to set email alerts
|

Particulate iron dynamics during FeCycle in subantarctic waters southeast of New Zealand

Abstract: [1] The FeCycle experiment provided an SF 6 labeled mesoscale patch of high-nitrate low-chlorophyll (HNLC) water in austral summer 2003. These labeled waters enabled a comparison of the inventory of particulate iron (PFe) in the 45-m-deep surface mixed layer with the concurrent downward export flux of PFe at depths of 80 and 120 m. The partitioning of PFe between four size fractions (0.2-2, 2-5, 5-20, and >20 mm) was assessed, and PFe was mainly found in the >20-mm size fraction throughout FeCycle. Estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
175
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(201 citation statements)
references
References 83 publications
(116 reference statements)
22
175
2
Order By: Relevance
“…Increases in the apparent solubility when considering the longer-term processing of lithogenic particles, similar to that for Th, have been reported for Fe (Boyd et al, 2010;Frew et al, 2006;Hansard et al, 2009). On this basis, we infer a general similarity in the dissolution of relatively insoluble lithogenic elements such as Fe, Nd, etc.…”
Section: Dissolved Metal Fluxes Based On Dissolved 232 Th Fluxesmentioning
confidence: 59%
“…Increases in the apparent solubility when considering the longer-term processing of lithogenic particles, similar to that for Th, have been reported for Fe (Boyd et al, 2010;Frew et al, 2006;Hansard et al, 2009). On this basis, we infer a general similarity in the dissolution of relatively insoluble lithogenic elements such as Fe, Nd, etc.…”
Section: Dissolved Metal Fluxes Based On Dissolved 232 Th Fluxesmentioning
confidence: 59%
“…In the lower panels, sites where simultaneous total 234 Th, large particle 234 Th, and large particle element measurements have been made are shown as filled squares (this study) and circles (Lemaitre et al, 2016;Planquette et al, 2011;Weinstein and Moran, 2005). Prior 234 Th studies where large particle E: 234 Th values were extrapolated from other data are indicated by diamonds (Bown et al, 2011;Dulaquais et al, 2014) and trap-only studies by nabla (Collier et al, 2000;Frew et al, 2006;Lamborg et al, 2008;Martin, 1990;Martin et al, 1985, 1980, Martin and Knauer, 1984, 1983Migon et al, 2002;Noble et al, 2012;Pohl et al, 2004;Quetel et al, 1993;Schüßler et al, 1997;Stanley et al, 2004). 234 Th.…”
Section: Discussionmentioning
confidence: 98%
“…Bishop et al, 1977;Frew et al, 2006;Weinstein and Moran, 2004) and often limited to a select few metals (e.g. Bishop and Fleisher, 1987;Lam et al, 2006) or a single location (e.g.…”
Section: Element Concentrations In Large Particlesmentioning
confidence: 99%
“…This implies either that seasonal dFe patterns in spring-summer are dominated by external inputs (mediated by physical mixing) or that the signal of biology is dominated by recycling terms. For example, a number of attempts to construct dFe budgets have highlighted the so-called "ferrous wheel" as the dominant Fe flux term (e.g., Strzepek et al, 2005;Frew et al, 2006;Boyd and Ellwood, 2010). The "ferrous wheel" encompasses Fe recycling processes associated with zooplankton grazing, higher trophic levels, bacterial turnover, as well as dissolution of particle Fe (e.g., Strzepek et al, 2005;Frew et al, 2006;Tovar-Sanchez et al, 2007;Nicol et al, 2010).…”
Section: Future Challengesmentioning
confidence: 99%
“…For example, a number of attempts to construct dFe budgets have highlighted the so-called "ferrous wheel" as the dominant Fe flux term (e.g., Strzepek et al, 2005;Frew et al, 2006;Boyd and Ellwood, 2010). The "ferrous wheel" encompasses Fe recycling processes associated with zooplankton grazing, higher trophic levels, bacterial turnover, as well as dissolution of particle Fe (e.g., Strzepek et al, 2005;Frew et al, 2006;Tovar-Sanchez et al, 2007;Nicol et al, 2010). While we might imagine greater herbivory and associated Fe recycling to be associated with higher Chl-a levels, which would then be in accord with the associated high values of dFe, we lack quantitative data.…”
Section: Future Challengesmentioning
confidence: 99%